Evolution of cooperation between SMEs in the footwear industry. An answer to global value chains and cost minimization - González Alvarado, Tania Elena; González Fernández, Sara (REVESCO. Revista de Estudios Cooperativos, 2017)
The aim of this article is to analyse the cooperation tie between small and medium enterprises in the footwear industry like a response to the global value chain and cost minimization. Statistics data from governments and research projects are analysed. 81 small and medium enterprises participating at the Al-Invest were studied. The principal result is that the cooperation tie is the development factor and the family is the genesis of generating value. The conclusion is that enterprise internationalization has a positive impact under the local system, only when the cooperation mechanism exists, including in poor economies with obstacles for innovation.
Keywords: Cooperation; microfirms; SME; strategic management; technology adoption; informal economy.